Biomechanical comparison of augmented versus non‐augmented sacroiliac screws in a novel hemi‐pelvis test model. Issue 7 (16th September 2016) - Grüneweller, Niklas; Raschke, Michael J.; Zderic, Ivan; Widmer, Daniel; Wähnert, Dirk; Gueorguiev, Boyko; Richards, Robert Geoff; Fuchs, Thomas; Windolf, Markus
ABSTRACT: Operative treatment of sacral insufficiency fractures is frequently being complicated by osteopenic bone properties. Cement augmentation of implanted sacroiliac screws may lead to superior construct stability and prevent mechanical complications. A novel hemi‐pelvis test model with dissected symphysis was developed. Five fresh‐frozen cadaveric pelvises were vertically osteotomized at the sacrum on both sides and fixed with sacroiliac screws in both corridors of the first sacral vertebral body. One side was randomly augmented with bone cement. Cyclic testing consisting of torsional loading (±2.5 Nm) combined with progressively increasing axial loading (+50 N compression, −10 N traction, ±0, 01 N/cycle) was performed until failure; simulated physiological loads derived from inverse dynamic calculations. The fixation was analyzed fluoroscopically quantifying screw migrations and assessing failure mechanisms. Failure modes were cut‐out, pull‐out, screw‐out, and washer penetration. Motion at fracture site was analyzed via optical motion tracking. Unscrewing was provoked four times with non‐augmented and twice with augmented screws. When focusing on the sacral region only, cement augmentation significantly improved screw fixation in terms of increased number of cycles to failure ( p = 0.043). However, when considering overall construct stability, there was no significant difference between augmented and non‐augmented state due to washer penetration at the iliac bone. The generated hemi‐pelvis model was found to be valid due to the reproduction of the clinically observed failure mode (unscrewing). Unscrewing was not fully prevented by cement augmentation. Augmentation effects stability at the screw tip, but particularly in porotic bone, failure may shift to the next weak point. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1485–1493, 2017. Abstract : A novel cadaveric hemi‐pelvis test model was developed. Pelvises were vertically osteotomized at the sacrum on both sides and fixed with sacroiliac screws, randomly augmenting one of the screws with bone cement while leaving the other one non‐augmented. Cyclic testing was performed until failure with application of physiological loading pattern. The fixation was analyzed fluoroscopically quantifying screw migrations and assessing failure mechanisms, such as unscrewing screw‐out, pull‐out and cut‐out. Unscrewing was not fully prevented by cement augmentation. Augmentation effects stability at the screw tip, but particularly in porotic bone, failure may shift to the next weak point.